Sultan Mehmed II (The Conqueror) (1451-1481 CE): His Conquering of Constantinople and Domestic Policy - Muhammad, Abdul Fattah Rajab Hamad (Al-Mukhtar Journal of Social Sciences, 2024)
Sultan Mehmed II, known as "The Conqueror," is considered one of the most prominent rulers of the Ottoman Empire from 1451 to 1481 CE. The conquest of Constantinople (Istanbul) was a significant achievement for him, and his domestic policy was also important. He ascended the throne at the age of fourteen and relied on advisors and ministers to assist him in governing the state. It is believed that his father, Sultan Murad II, instilled in him the desire to conquer Constantinople and expand the Ottoman domain. The Pope and the King of Hungary formed a Crusader alliance to attack the Ottoman Empire, but Mehmed II summoned his father to return and help him confront this challenge. In the Battle of Varna, the Ottoman army managed to defeat the Crusader alliance and kill the King of Hungary. Subsequently, the commander Hunyadi attempted to organize a new Crusade, but Sultan Mehmed II confronted and achieved a significant victory in the Battle of Kosovo. This triumph foiled the Europeans' plans to expel the Ottomans from the Balkans for a long period. Sultan Mehmed II passed away in 1481 CE.
Keywords: Mehmed The Conqueror; Constantinople; The Ottoman Empire; The Crusade; Battle of Kosovo